A Statistical Test for Ripley's K Function Rejection of Poisson Null Hypothesis. (14th April 2013) - Marcon, Eric; Traissac, Stéphane; Lang, Gabriel
Abstract : Ripley'sK function is the classical tool to characterize the spatial structure of point patterns. It is widely used in vegetation studies. Testing its values against a null hypothesis usually relies on Monte-Carlo simulations since little is known about its distribution. We introduce a statistical test against complete spatial randomness (CSR). The test returns theP value to reject the null hypothesis of independence between point locations. It is more rigorous and faster than classical Monte-Carlo simulations. We show how to apply it to a tropical forest plot. The necessary R code is provided.